Sustainable development : economics and policy - Rao, P. K. (Malden, Mass. ; Oxford : Blackwell, 2000)
This book is about: A brief history; Resources and the environment; Sustainable development; Valuing resources and the future; Managing the global commons; Environmental accounting; ...
Keywords: Economics; Environmental policy; Environmental policy; Sustainable development